Performance Evaluation and Modeling of L1 GPS Receiver and Signal Tracking - Abdullah Khalid Ahmed; Mohammed AlMahamdy; Naser Al-Falahy (Tikrit Journal of Engineering Sciences)
Direct Sequence Spread Spectrum (DSSS) has high immunity against noise due to the great spreading gain of the pseudo-noise (PN) code. The Global Positioning System (GPS) satellites send navigation messages at the L1 frequency band, where coarse acquisition codes are embedded within these messages. Two scenarios are evaluated for navigation data tracking: phase tracking and code tracking processes. The coded data is recovered, and the carrier is removed using a phase tracking loop. The DLL (Delay-Locked Loop) retrieves the navigation data for code synchronization. This paper aims to model an L1 GPS signal receiver and assess its performance in both the time and frequency domains. The processing of this evaluation is regarding input dynamics such as Doppler and noise. This study emphasizes the importance of the Gold code with respect to cross-correlation and autocorrelation compared to the traditional PN coding. When it comes to wireless networks, Gold code is an interesting option since it can produce a more restricted and stable spectrum than PN code. The results demonstrate how a DLL with a narrow bandwidth may still decode data even if the system loses tracking, giving the system a higher level of reliability.